Representações posit(hiv)as na literatura juvenil brasileira: uma análise de o dono dos pés (1996), de Jussara Rocha Koury - Moraes, Isaque da Silva (2024)
The last two decades of the 20th century was a period of huge transformation in the cultural scenario in Brazil. In the literary field, for example, we had a maturation and consolidation of literature aimed at young people, through the instances of consecration, the increase in the production of texts and the distinction of authors who have given this focus to their books. In parallel with this fact, in the social scenario the epidemic of HIV/aids emerged, which generated political, educational and cultural responses from various spheres of society. Related to this, various literary texts have emerged with the theme in question, since the relationship between literature and society is intrinsic, as Candido ([1965] 2023) pointed out. This research aims to understand the representations of HIV/aids in the youth novel O dono dos pés (1996), by Jussara Rocha Koury. Specifically, the aims of the study are: i) to investigate the Brazilian scene in the 1990s; ii) to carry out a historical overview of works with this theme; iii) to point out how the inclusion of this and other themes helped to consolidate such literature and the erasure of texts in literary criticism; iv) to produce material for the author's critical fortune; v) to compare the editions of the book that make up the corpus; and vi) to analyse how the novel was thematised and its approach within the scope of teen sick-lit. As a methodological approach, the study takes a qualitative approach and follows the dialectical method, since it investigates the emergence and transformations of this theme in youth literature, and, to this end, data was technically collected from bibliography and documents. To gather data on the writer an episodic interview was conducted (Flick, 2013), in which she narrated events directly related to the core of the research. Our theoretical framework is based on two main fields: a) studies on youth literature and the thematization of diseases in these texts, with authors such as Coelho (1991), Lacerda (1998), Ceccantini (2000), Souza (2006), Gregorin Filho (2011), Elman (2012), Souza (2015), Silveira and Silveira (2016; 2019) and Lajolo and Zilberman (2022); and b) theoretical-critical studies on the relationship between literature and HIV/aids, based on scholars such as Bessa (1997; 2002), Moriconi ([2006] 2020), Sousa (2015a; 2015b; 2016), Inácio (2016), Fonseca (2022; 2023), among others. The results of the study were: to have knowledge (i.e. being aware of) of Brazilian youth literature on HIV/aids, published in print, between 1980 and 2020; to understand the context of the emergence and transformations of the representation of HIV/aids in this literature; the aspects that led to the erasure of these works in theoretical-critical studies; the development of critical procedures to broaden relations between the fields; and the delineation of the specificities of this literary production in Brazil; indicators for the author's critical fortune; the identification of the particularities of the editions of the youth novel and their effects of meaning; and the multifaceted arrangement of HIV/aids present in the narrative, even precipitating aspects of the thematic handling that followed with the advance of understanding about the virus and the disease.